2018
DOI: 10.1038/s41598-018-23396-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biological Characteristics of Mesenchymal Stem Cells Derived from the Human Placenta and Umbilical Cord

Abstract: Mesenchymal stem/stromal cells (MSCs) derived from placental tissue show great therapeutic potential and have been used in medical treatment, but the similarity and differences between the MSCs derived from various parts of the placenta remain unclear. In this study, we compared MSCs derived from different perinatal tissues, including the umbilical cord (UC), amniotic membrane (AM), chorionic plate (CP) and decidua parietalis (DP). Using human leukocyte antigen (HLA) typing and karyotype analysis, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 47 publications
5
118
2
1
Order By: Relevance
“…Many groups have shown the anti-keloid effects of MSCs [33,34,49,50], but one study showed that MSCs derived from the subamniotic membrane of the umbilical cord showed enhanced keloid fibroblast growth in vitro [51], with no confirmatory studies in in vivo preclinical animal models. Given the differences in stemness properties of cells between subamnion and Wharton's jelly compartments [9,52], it is possible that these different responses are due to differences in the secretome of the two cell types because of their different embryological development, cell form, and function. Additionally, the different ethnic sources of the keloid cells used in the studies may also account for the differences in anti-keloid behavior because the enhanced keloid cell growth by subamniotic membrane stem cells was observed in Caucasian samples while the keloid inhibitory effects observed with Wharton's jelly stem cells was on Asian samples.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have shown the anti-keloid effects of MSCs [33,34,49,50], but one study showed that MSCs derived from the subamniotic membrane of the umbilical cord showed enhanced keloid fibroblast growth in vitro [51], with no confirmatory studies in in vivo preclinical animal models. Given the differences in stemness properties of cells between subamnion and Wharton's jelly compartments [9,52], it is possible that these different responses are due to differences in the secretome of the two cell types because of their different embryological development, cell form, and function. Additionally, the different ethnic sources of the keloid cells used in the studies may also account for the differences in anti-keloid behavior because the enhanced keloid cell growth by subamniotic membrane stem cells was observed in Caucasian samples while the keloid inhibitory effects observed with Wharton's jelly stem cells was on Asian samples.…”
Section: Discussionmentioning
confidence: 99%
“…Exemplifying this are the discovery that MSCs can also differentiate into cells of ectodermal and endodermal parentage (Wei et al, 2013) and the inclusion of novel surface markers to their identity (CD165, CD276, and CD82) (Al-Nbaheen et al, 2013). Several studies on MSC lineages have also identified distinctive molecular (Al-Nbaheen et al, 2013;Ullah et al, 2015;Wu et al, 2018), proliferation/differentiation (Kern et al, 2006), and functional properties (Keyser et al, 2007), accrediting the fact that their biology is still partially intelligible. The conventional notion, however, is that MSCs are (i) genomically stable, (ii) highly accessible, (iii) easy to isolate and expand, (iv) immuneprivileged (low expression of MHC I/II and co-stimulatory molecules and -further explained in Section "Immunological Properties: A Paradigm" -immunomodulation), and -unlike other types of stem cells -(v) non-teratogenic and ethically conforming (Wei et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(b) Providing cells from a suitable source, as different sources conceive different end‐products after following the same bioprocess. Work from Wu et al () found that closely related cells from various parts of prenatal tissue present different phenotype, multilineage differentiation potential, expansion capacity, and level of expression of several paracrine factors. These phenotypic differences increase when comparing cells from unrelated sources (Bonaventura et al, ; Shi, Robey, & Gronthos, ).…”
Section: Introductionmentioning
confidence: 99%